N. BURKŠAITIENĖ AND J. ŠLIOGERIENĖ‘S MONOGRAPH „ASSESSMENT AND RECOGNITION OF THE ACHIEVEMENTS OF NON-FORMAL AND SELF-DIRECTED LEARNING AT UNIVERSITIES“ - Bulajeva, Tatjana (Acta Paedagogica Vilnensia, 2011)
...